Cognitive Load Theory and Mathematics Learning: A Systematic Review - Aditomo, Anindito (Faculty of Psychology, Universitas Surabaya, 2009)
Cognitive load theory (CLT) is an instructional design theory which is based on an information processing view of human cognition. Recently, proponents of this theory have claimed that all forms of “minimally-guided instruction” lead to poorer learning compared to direct instruction because they impose irrelevant cognitive load. This article critically examines this claim by reviewing the empirical evidence that it is based on. This review focuses on studies of mathematics learning. This review concludes that there is little evidence to support the strong claim made by cognitive load theory. Theoretical and practical implications of this finding are discussed. Teori beban kognitif adalah teori perancangan pembelajaran yang didasarkan pada teori pemrosesan informasi tentang kognisi. Belum lama berselang, beberapa ahli teori beban kognitif menyatakan bahwa semua metode pembelajaran yang mengharuskan siswa untuk memecahkan masalah secara mandiri (minimally-guided instruction) akan membawa hasil belajar yang lebih buruk bila dibandingkan metode-metode pengajaran langsung seperti ceramah atau belajar dari contoh soal. Klaim inilah yang diulas secara kritis dalam artikel ini. Untuk mempersempit permasalahan, ulasan ini hanya akan membahas pembelajaran di bidang matematika. Ulasan ini menemukan sedikit bukti yang mendukung klaim yang dikemukakan para ahli teori beban kognitif. Implikasi teoretis dan praktis dari temuan akan dibahas.